Hugh Esmor Huxley MBE. 25 February 1924 — 25 July 2013. (31st December 2017) - Holmes, Kenneth C.; Weeds, Alan
Abstract : Hugh Esmor Huxley devoted his life to understanding how muscles contract. He was born in Birkenhead and entered Christ's College, Cambridge, in 1941 to study Physics. Joining the RAF in 1943 as an Acting Pilot Officer, he later moved to the Malvern Telecommunications Research Establishment where his pioneering work on developing H2 S Mk IVA airborne radar over two years to 1947 led to his being elected a Member of the Order of the British Empire in 1948 while still an undergraduate. He started X-ray research on living muscle with Sir John Kendrew at the Medical Research Council Unit in the Cavendish Laboratory and showed that skeletal muscle is made of a hexagonal array of thick and thin filaments. In 1952 he moved to the Massachusetts Institute of Technology (MIT) to study muscle ultrastructure by electron microscopy, where he was joined by Jean Hanson, and in 1954 they published the sliding filament hypothesis (7) † . Back in London he produced ultra-thin sections of muscle barely 150 Å thick, which showed cross-bridges between the filaments, and in 1960 was elected a Fellow of the Royal Society. His research at the MRC Laboratory of Molecular Biology from 1962 led to his proposal of the swinging cross-bridge model. His ambition of studying cross-bridge movement in living muscle by X-ray diffraction in the millisecond time range required ever stronger X-ray sources and more sensitive detectors. The development in the 1970s of beam lines from synchrotron radiation opened a new perspective that fascinated him for the rest of his working life. From his last work at Argonne National Laboratory with Massimo Reconditi, Hugh finally convinced himself that he had incontrovertible evidence for the tilting lever-arm model.